2014
DOI: 10.1155/2014/762397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial, Antifungal, and Antioxidant Activities of Safflower Natural Dyes during Flowering

Abstract: Two Carthamus tinctorius varieties (Jawhara and 104) were studied in order to investigate their natural dyes contents and biological activities. Obtained results showed that quinochalcone contents and antioxidant activities varied considerably as function of flowering stages. So flowers at fructification stage contained the highest carthamin content with the strongest antioxidant capacity with all assays (FRAP, DPPH, and chelating power methods). In parallel, we showed a decrease in the content of precarthamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…According to Cai, Luo, Sun, and Corke (2004), several phenolic components, such as flavonoids (carthamin and carthamone) and lignans, are present in the safflower petal. Recently, Salem et al (2014) reported ferric reducing ability, radical scavenging activity, and metal chelating powder of carthamin and suggested that carthamin could be a strong natural antioxidant. Thus, carthamin contained in WFC could act as a reductant and might be associated with increased nitrosoheme pigments formation at an equal amount of nitrite.…”
Section: Nitrosoheme and Residual Nitrite Contents Of Cooked Sausagesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Cai, Luo, Sun, and Corke (2004), several phenolic components, such as flavonoids (carthamin and carthamone) and lignans, are present in the safflower petal. Recently, Salem et al (2014) reported ferric reducing ability, radical scavenging activity, and metal chelating powder of carthamin and suggested that carthamin could be a strong natural antioxidant. Thus, carthamin contained in WFC could act as a reductant and might be associated with increased nitrosoheme pigments formation at an equal amount of nitrite.…”
Section: Nitrosoheme and Residual Nitrite Contents Of Cooked Sausagesmentioning
confidence: 99%
“…After refrigerated storage of seven days, similar tendencies were continuously maintained. Recent studies have reported antioxidant effect of safflower petal, based on results of ferrous reducing, radical scavenging, and metal chelating assays (Hiramatsu, Takahashi, Komatsu, Kido, & Kasahara, 2009;Salem et al, 2011;Salem et al, 2014). Although the mechanism of antioxidant effect of WFC was not clear, our result suggested that the carthamin contained in WFC Nitrite level (N) *** *** *** *** *** WFC level (W) *** *** *** *** *** Interaction N Â W * ** ** *** *** aef Values with different letters within a column of each treatment are significantly different (P < 0.05).…”
Section: Lipid Oxidation Of Cooked Sausagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Salem et al (2014) successfully extracted natural pigment from Carthamus tinctorius. The pigments displayed antimicrobial activity against MethicillinResistant Staphylococcus aureus (MRSA), Escherichia coli ATCC 25218 and Candida albicans.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that HSYA offers protection against mitochondrial injury in cerebral ischemic due to scavenging of oxygen free radicals, inhibition of lipid peroxidation and antagonism of Ca 2+ [28] . It should be noted that quinochalcone contents in safflower and its antioxidant activities vary considerably as a result of fluctuating flowering stages [29] . The extract of Rhizoma Chuanxiong is a robust scavenger of superoxide anions and inhibitor of lipid peroxidation, with a strong dose-response relationship within a narrow concentration range.…”
Section: Use Of Natural Antioxidants In the Prevention And Treatment mentioning
confidence: 99%